Chronic obstructive pancreatitis due to a pancreatic cyst in a patient with autosomal dominant polycystic kidney disease. Issue 1 (1st January 1998) - Malka, D; Hammel, P; Vilgrain, V; Fléjou, J-F; Belghiti, J; Bernades, P
Abstract : Background —Autosomal dominant polycystic kidney disease, the most frequent inherited polycystic disease, is a systemic disorder characterised by the development of numerous and bilateral kidney cysts leading to chronic renal failure. Extrarenal cysts are located mainly in the liver but also in various organs including the pancreas. To our knowledge, complications of pancreatic cysts in this disease have never been reported. Patient —The first case of painful chronic obstructive pancreatitis due to a true pancreatic cyst in a patient with autosomal dominant polycystic kidney disease is reported. Abdominal transparietal and endoscopic ultrasonography, computed tomography, and endoscopic retrograde cholangiopancreatography showed a cystic lesion in the body of the pancreas associated with upstream dilatation of the main pancreatic duct. Intraoperative ultrasonography before and after cyst fluid aspiration, and pancreatography and pathological examination of the resected distal pancreas confirmed that both main pancreatic duct enlargement and chronic pancreatitis were caused by a benign cyst. Conclusion —Chronic obstructive pancreatitis should be added to the extrarenal complications of autosomal dominant polycystic kidney disease.